Barriers to the early integration of palliative care in pediatric oncology in 11 Eurasian countries. Issue 22 (19th August 2020) - Ehrlich, Bella S.; Movsisyan, Narine; Batmunkh, Tsetsegsaikhan; Kumirova, Ella; Borisevich, Marina V.; Kirgizov, Kirill; Graetz, Dylan E.; McNeil, Michael J.; Yakimkova, Taisiya; Vinitsky, Anna; Ferrara, Gia; Li, Chen; et al.
Abstract : Background: The early integration of palliative care significantly improves quality of life for children with cancer. However, cultural, structural, and socioeconomic barriers can delay the integration of palliative care into cancer care, particularly in low‐income and middle‐income countries. To date, little is known regarding the timing of and barriers to palliative care integration in Eurasia. Methods: The Assessing Doctors' Attitudes on Palliative Treatment (ADAPT) survey evaluates physician perceptions regarding palliative care integration into pediatric oncology in Eurasia. This evidence‐based survey was adapted to the regional context; iteratively reviewed by US and regional panelists; and piloted in English, Russian, and Mongolian. After distribution to physicians caring for children with cancer, statistical analysis was complemented by qualitative analysis of open‐ended responses. Results: A total of 424 physician responses were received from 11 countries in the Eurasian region. Study findings demonstrated wide variability in access to palliative care experts across countries (18%‐96%), with the majority of providers (64%) reporting that the initial palliative care consultation typically occurs when curative options are no longer available. Providers desired an earlier initial palliative care consultation than what currently occurs in their setting ( P < .001). Primary barriers to timely consultation included limited access to palliative care services and specialists, lack of physician education, and perceived family resistance. Conclusions: The current study is the first to identify physician perceptions of the delayed timing of palliative care integration into childhood cancer care and associated barriers in Eurasia. These findings will inform the development of targeted interventions to mitigate local structural and cultural barriers to access and facilitate earlier palliative care integration in the region. Abstract : The current study is the first to identify physician perceptions of the delayed timing of palliative care integration into childhood cancer care in Eurasia. Primary barriers to timely consultation included limited access to palliative care services and specialists, a lack of physician education, and perceived family resistance.